Blockchain Solutions for Enhancing Security and Privacy in Industrial IoT - Meryam Essaid; Hongtaek Ju (Applied Sciences, 2025)
The Industrial Internet of Things (IIoT) has revolutionized smart manufacturing by enhancing automation, operational efficiency, and data-driven decision making. However, the interconnected nature of IIoT devices raises significant concerns about security and system integrity. This paper examines the application of blockchain technology to address these challenges, with a focus on data integrity, access control, and traceability. This paper proposes a blockchain-based framework that leverages decentralized security, smart contracts, and edge computing to mitigate vulnerabilities, including unauthorized access and data manipulation. The framework is evaluated for practicality, scalability, and constraints within IIoT environments. Additionally, this paper discusses the integration of complementary security mechanisms, such as Zero Trust architecture and AI-driven anomaly detection, to provide a comprehensive cybersecurity solution for the Industrial Internet of Things (IIoT).